Analysis of the Implementation of the Online Single Submission System in NIB Services on the Growth of MSMEs Businesses in Padang Siempuan City - Anisah Nasution; Muhammad Ikhsan Harahap; Muhammad Lathief Ilhamy Nasution (Jurnal Manajemen Bisnis, 2024)
The Government Regulation issued by President Joko Widodo on June 21, 2018, which regulates the Online Single Submission (OSS), faces various obstacles in its implementation. These obstacles involve business actors and agencies responsible for permits within the OSS. One of the main obstacles is the lack of understanding regarding the use of the OSS system. Meanwhile, in Padang Sidempuan City, there are 10,641 MSMEs in Padang Sidempuan based on data from December 2022, and from the initial research data, it turns out that many are still unaware of the OSS and do not have an NIB. This research is a qualitative study using a descriptive approach, in the form of field research. The results of this study indicate the absence of the Impact of OSS Implementation and Business Identification Number on the Growth of Sharia Businesses in Padang Sidempuan City. The reasons for this are that Sharia business actors do not know how to use the OSS System and are also unaware of the benefits of having a Business Identification Number.